2008
DOI: 10.1103/physrevb.78.155310
|View full text |Cite
|
Sign up to set email alerts
|

Complex domain-wall dynamics in compressively strainedGa1xMnxAsepilayers

Abstract: The domain-wall-induced reversal dynamics in compressively strained Ga 1−x Mn x As was studied employing the magneto-optical Kerr effect and Kerr microscopy. Due to the influence of a uniaxial part in the in-plane magnetic anisotropy 90°Ϯ ␦ domain walls with considerably different dynamic behavior are observed. While the 90°+ ␦ reversal is identified to be propagation dominated with a small number of domains, the case of 90°−␦ reversal involves a larger number of nucleation centers. The domain-wall nucleation/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Very recently single DWs have been resolved in the static limit by means of electron holography on the scale of a few micrometers [6] with high spatial resolution. In contrast, we have shown that Kerr microscopy provides full time and spatially resolved information on the dynamics of in-plane magnetic domains during the magnetization reversal on the scale of a few hundred micrometers [7]. Due to the low Curie-temperatures T c well below room temperature of most ferromagnetic semiconductors like GaMnAs it is of technical interest to study these materials in the highest possible temperature range just below T c .…”
mentioning
confidence: 96%
“…Very recently single DWs have been resolved in the static limit by means of electron holography on the scale of a few micrometers [6] with high spatial resolution. In contrast, we have shown that Kerr microscopy provides full time and spatially resolved information on the dynamics of in-plane magnetic domains during the magnetization reversal on the scale of a few hundred micrometers [7]. Due to the low Curie-temperatures T c well below room temperature of most ferromagnetic semiconductors like GaMnAs it is of technical interest to study these materials in the highest possible temperature range just below T c .…”
mentioning
confidence: 96%
“…17 Using the time-resolved MOKE, laser pump-probe experiments enable the investigation of magnetization dynamics in the femtosecond to nanosecond range, in particular, the coherent collective magnetic excitations. 6,18,19 Magneto-optical microscopy uses the MOKE to gain insight into the magnetic domains static pattern 7,20,21 and the domain wall dynamics. 22 While the MO effects in (Ga,Mn)As have been extensively investigated, [13][14][15][16][23][24][25][26][27][28][29][30][31][32][33][34] the MO properties of (Ga,Mn) (As,P) thin films, more specifically the interplay between the Mn doping and P substitution, remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The (Ga,Mn)As samples used in this work were grown by molecular beam epitaxy (MBE) on a semi-insulating GaAs substrate. 9 The manganese concentrations in the samples employed, designated A and B, are 1.2% and 3%, with thicknesses 170 and 40 nm, respectively. Magnetotransport measurements have been carried out using 30-μm-wide Hall bar devices patterned along the hard [110] direction by standard photolithography.…”
mentioning
confidence: 99%